Pedagogical support and teaching performance of teachers of network 08 at the primary level, UGEL 04 de Comas, Lima, 2024 - Dávila Boluarte, Victoria Volodia (2024)
This research examined the relationship between pedagogical accompaniment and teacher performance in three schools of the Red 08 network in Puente Piedra, Lima, Peru. A questionnaire was administered to 48 teachers to measure their perception of pedagogical accompaniment and their self-assessment of teaching performance. The results revealed a high reliability of the measurement instrument (Cronbach's alpha > 0.94) and moderate positive correlations between PA and two specific dimensions of TP: preparation for student learning and teaching for student learning. However, no significant relationship was found between pedagogical accompaniment and overall teacher performance. These findings suggest that pedagogical accompaniment can positively influence specific aspects of teaching practice, but its impact on overall performance may be attenuated by other factors. The implications of these results are discussed in relation to previous literature, and recommendations are proposed to strengthen pedagogical accompaniment in the Red 08 network in Puente Piedra, promoting more participatory, contextualized, and formative feedback-centered approaches. The need for future research to better understand the relationship between pedagogical accompaniment and teacher performance in the Peruvian context and to design strategies that respond to the specific needs of teachers and schools is highlighted.